Zethus (Zethus) pilosus Zavattari, 1912 (Hymenoptera: Vespidae: Eumeninae) from Southern Brazil: description of the female, the male genitalia, its nest and notes on biology - Lopes, Rogério Botion; Brozoski, Franciele; Buschini, Maria Luisa Tunes (Zootaxa, 2019)
Zethus is the largest vespid genus and, despite being very diverse in the Neotropical region, little is known about its biology and many species are known from only one sex. Zethini are centered in one of the controversies involving Vespidae phylogeny; increased knowledge of terminals will allow for more precise analyses, because some phylogenetically informative characters are observed in only one sex and others can be extracted from nests. With this in mind, complementary knowledge on Zethus pilosus is presented: the description of the female, of the male genitalia, of the nest and notes in its biology. Additional key features in the pronotum for identification of this species are provided. Nests were founded between December and April, presenting construction of partitions out of a combination of mud, sand, vegetable matter and insect parts. Development from egg to adult lasted an average of 39 days.